Localization of phospholamban in smooth muscle using immunogold electron microscopy (The Rockefeller University Press, 1988)
Phospholamban, the putative regulator of the Ca2+-ATPase in cardiac sarcoplasmic reticulum, was immunolocalized in canine visceral and vascular smooth muscle. Gently disrupted tissues were labeled with an affinity-purified phospholamban polyclonal antibody and indirect immunogold, using preembedding techniques. The sarcoplasmic reticulum of smooth muscle cells was specifically labeled with patches of immunogold distributed in a nonuniform fashion, while the sarcolemma did not appear to contain any phospholamban. The outer nuclear envelopes were also observed to be heavily labeled with the affinity- purified phospholamban polyclonal antibody. These findings suggest that phospholamban may play a role in the regulation of cytoplasmic and intranuclear calcium levels in smooth muscle cells.